Socioeconomic factor and first-degree graduate employability: The Malaysian scenario - Md Nor, Sharifah; Abu Samah, Bahaman (The International Journal of Diversity in Organisations, Communities and Nations, 2009)
This paper discusses graduates’ employability and its relationship to socioeconomic factor. Approximately 2048 first-degree graduates from the public universities were studied. Graduates were surveyed online regarding their employment status (being employed or unemployed, current earning and job status) soon after they completed their degree and two years later. Descriptive statistics including logistic regression were utilized as tools of analysis. The findings reveal that graduates’ socioeconomic status as measured by their family income is related to their employability status both soon after graduation and two years later. Discussions pertaining to possible reasons for this phenomena and measures to enhance the employability of graduates from poorer homes was discussed.